Terror trail - Compton, Ralph; Brandt, Lyle, 1951- (Compton, Ralph. Trail drive series., 2021)
With their father injured and their brother murdered, the Aguirre twins--Dolores and Yolanda--lead a crew of ranch hands and friendly members of the Mescalaro Apache tribe to recover their herd--a perilous journey that brings about swift justice.